Study on comfort ability in classrooms in UiTM Shah Alam based on humidity / Muhammad Nur Ariff Zamhari - Zamhari, Muhammad Nur Ariff (Faculty Architecture, Planninng and Surveying, 2015)
This study was produced based on my selection of topic which is Study on Comfortability in Classrooms in UiTM Shah Alam Based on Humidity. The humidity is one of the important properties of the urban climate that has implications towards the human comfort, health, productivity and much more. They are essential components of a comfortable environment. Nowadays, the level of humidity in a room often neglected resulting certain impacts towards student’s comfortability. In summary, this study is briefly explained about the best way to improve the comfortability of user by controlling the humidity levels. The humidity level of all the classrooms can be made known by conducting a test using appropriate equipment and the comfortability of users is made known by distributing a list of questionnaires to the target respondents. The objectives of this study are to identify whether the humidity level in the classrooms at various faculty in UiTM Shah Alam met the optimum value; to analyse the comfortability of users in each classroom; and to recommend the best way to improve the comfortability of users. As conclusion, I am hoping that the contents of this study are able to explain regarding on this topic in more details, easy to understand and useful to others in need.